ANALYSIS OF PRIORITY CUSTOMER SATISFACTION AND LOYALTY IN BANK BUMN WITH GROUNDED THEORY QUALITATIVE ANALYSIS METHOD - Galih Kusumo; Arief Bimantoro Suharko (Sean Institute, 2023)
This study aims to study the phenomenon of priority customer satisfaction and loyalty in the banking industry, especially at a branch office of a state-owned bank in Indonesia. This research studies and identifies the reasons for priority customers to transfer their funds to other banks. Researchers used the Grounded Theory analysis method, as an instrument for qualitative analysis. Researchers conducted in-depth interviews with six customers who had transferred their funds to the bank. The analysis performed consisted of open coding of the data to identify categories and themes; axial coding to link categories and themes; and selective coding to identify core themes. The findings show that service quality is the main factor that constructs customer loyalty and satisfaction. Analysis of categories and themes based on axial coding shows that the theme of service quality is connected to all other themes across the range of dimensions. In addition, researchers found from interviews that service features are a core category of service quality and a factor of customer satisfaction and loyalty. Thus, Service Quality acts as a central theme in this study. Good service quality will create a feeling of security and comfort for customers to continue making transactions so they will not move to other banks.